Burned areas and changes in land uses in southwest Chihuahua, México, during 2013-2017: Identification with the normalized burn ratio index (NBR) - Valdez-Zavala, K. M.; Bravo Peña, L. C.; Manzo Delgado, L. L. (Acta Universitaria, 2019)
Fires are a problem on forest ecosystems, affecting the natural diversity. Currently, several spectral indices have been implemented for the identification of burned areas. In this study, burned areas and transitions of land use were identified and quantified in the southwest of Chihuahua, Mexico, by the normalized burn ratio index (NBR) obtained from 28 satellite images. The NBR identified 1260.73 ha of burned areas; 1030.12 ha showed change in vegetation coverage and land use, while the remaining area keep unchanged. In polygons with change, a transition from forest cover to secondary vegetation was observed, while the polygons without change maintained their original agricultural coverage. The method used facilitates the monitoring and environmental management of affected areas by fire in Chihuahua, and it can be replicated in regions with similar conditions.